Factors Influencing Intention To Consume Herbal Supplement - SYED MOHAMED, ABBAS (2004)
The recent growth of herbal industry in Malaysia intensifies the challenges among market players. The main ingredient to be successful in the competitive industry is to be customer-oriented and market-driven. This research aims to contribute to the general understanding of consumer behavioral intention towards choice preferences, and to assist marketers in determining factors that influence consumers’ intention towards herbal supplement.